All this, and Heaven too [videorecording (DVD)] - Litvak, Anatole, 1902-1974; Davis, Bette, 1908-1989; Boyer, Charles, 1899-1978; Lynn, Jeffrey, 1909-1995; O'Neil, Barbara, 1910-1980; Field, Rachel, 1894-1942 (Bette Davis collection, 2008)
Henriette is the governess at the Paris home of the Duc de Praslin and his jealous wife. When governess and nobleman are drawn to each other, the Duchess erupts in fury and meets a bloody fate. Soon Henriette and the Duc face a world eager to believe the Duc murdered his wife and that the gentle Henriette was a willing accomplice.